CLINICAL SIGNIFICANCE AND PROGNOSTIC VALUE OF LOW MOLECULAR WEIGHT ‘TUBULAR’ PROTEIN, APHA-1-ACID GLYCOPROTEIN IN DIABETES - Raana, Gul e; Khurhsid, Rukhshan; Rasheed, Asma; Aftab, Muhammad Latif (Pakistan Journal of Physiology, 2009)
Back Ground: Tubular damage as suggested by tubular proteinuria is a recognized feature of glomerulonephritis in diabetics. Study Design: Study endeavoured to find out the level of alpha-1-acid glycoprotein (AGP) in urine of diabetic patient and tired to correlate the functional outcome of AGP with the patterns of proteinuria. Material and Methods: Fifty registered Type II diabetic patients were studied. Patients were divided on the basis of age into group A (41–60 yrs) and group B (>60 yrs) admitted in medical and visited the out door department of Sir Ganga Ram Hospitals, Lahore were included in the study. Duration of study was period of one year (from Jan 2005 to Jan 2006). Twenty normal subjects with no history of diabetes were taken as controls. Main Outcome Measures: Blood and urine samples of patients were collected and estimated the pH, specific gravity and protein level by strip and chemical method. Level of urinary AGP was found by using the technique of SDS gel electrophoresis. Level of blood glucose was estimated by auto analyzer. Results: Comparison of biochemical and other parameters in different age group of diabetics with normal subjects was carried out. Mean age of group A was 50 yrs and of group B was 65.80 yrs. The pH of urine was low in both groups as compared to normal subjects. A slight change in the specific gravity of urine was observed in group B and normal subjects while specific gravity of urine of group A was similar to normal control. Although the level of urinary protein of group A and B was greater than normal subjects but this shows no significant difference. Average raw volume of AGP was markedly increased in both groups A and B as compared to normal subjects. Level of blood sugar was significantly increased in group B as compared to group A. Conclusion: The best predictive value for either CRF outcome or for response to therapy was provided by the level of AGP. By screening this marker protein we may able to prevent or delay the progression of the disease.